The Ability of Islamic Cultural History Teachers in Managing the Classroom: A Review of Preventive and Repressive Measures - Iqbal, Maulana; Ahmadi, Ahmadi; Abdullah, Abdullah (Kamaya: Jurnal Ilmu Agama, 2025)
One of the abilities that must be possessed by a teacher is to manage the class well so that it can create a conducive learning atmosphere, good classroom management can be done by teachers by taking preventive and repressive actions. This study aims to determine the preventive and repressive actions taken by Islamic Cultural History teachers at MAN Kota Palangka Raya in managing the classroom. This research uses qualitative research with data collection techniques in the form of observation, interviews, and documentation. As for the data sources in this study conducted by researchers consist of two parts, namely primary data sources and secondary data sources. The Islamic Culture History subject teacher of MAN Kota Palangka Raya became the research subject, while the deputy head of madrasah and students as informants in this study. The results of this study indicate that in managing the classroom good teacher skills are needed, such as teachers can show responsiveness and attention to all students, teachers can also prepare lesson plans using a variety of methods so that students are more motivated to learn, especially Islamic Cultural History subjects. The teacher's ability in preventive action can also be done by adding class rules agreed upon by all class members and providing positive behavior reinforcement. As for repressive actions taken by MAN Kota Palangka Raya teachers in Islamic Cultural History lessons, namely by giving verbal warnings to students who behave poorly and educational sanctions to problematic students so that teachers can also take an individual approach. So it can be concluded in this study that the teacher's ability to manage the class is very necessary in learning.